34.696(x)+36.966(1-x)=35.453

Simple and best practice solution for 34.696(x)+36.966(1-x)=35.453 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 34.696(x)+36.966(1-x)=35.453 equation:



34.696(x)+36.966(1-x)=35.453
We move all terms to the left:
34.696(x)+36.966(1-x)-(35.453)=0
We add all the numbers together, and all the variables
34.696x+36.966(-1x+1)-(35.453)=0
We add all the numbers together, and all the variables
34.696x+36.966(-1x+1)-35.453=0
We multiply parentheses
34.696x-36.966x+36.966-35.453=0
We add all the numbers together, and all the variables
-2.27x+1.513=0
We move all terms containing x to the left, all other terms to the right
-2.27x=-1.513
x=-1.513/-2.27
x=1/1.5003304692664

See similar equations:

| X2+2y=0 | | -10.4z+1.6=-42.9-1.5z | | (7x1)=(6x+8) | | 1+|8+3n|=3 | | (x-15)=(x+25) | | 4x+4+96=180 | | -1/3g=5 | | (x+96)=(3x-92) | | 2x=7-3x=61 | | (4x+3)(x-2)=42 | | 13(11)-33=10(11)+5y | | 3x+5+8x+10=180 | | 7x-1=160 | | 3x+5=8x+10=180 | | (x+20)=(x-15) | | 18x+3=81 | | x^3+4x^2−7x−10=0 | | x/2.6=4 | | 0.5(10x+8)=26+3x | | d-5/9=3 | | 5x-4=14-4x | | -(b/6)-50=-49 | | 8/3x+1/3x=2*2/3+5/3x | | 9x-44=333 | | .8(20x-10)=0.75(16-32x) | | 10x-23=6x-26+79 | | 3(9x+13)=2(4x+10) | | 85+75x=100+45x | | 2x-8.7=5.5 | | 10x-23=6x-26 | | 6=-0.4y | | 4x-5+7x=13 |

Equations solver categories